OTIMIZAÇÃO E VALIDAÇÃO DE MÉTODOS DE DETECÇÃO DE Sclerotinia sclerotiorum EM SEMENTES DE SOJA E CANOLA, BASEADOS NA AMPLIFICAÇÃO LAMP - Grabicoski, Edilaine Mauricia Gelinski (2016)
Sclerotinia sclerotiorum infect many plants, including crops of great economic importance as soybeans (Glycine max) and oilseed rape (Brassica sp.), responsible for great losses. The plant disease control is the most important practical objective of plant pathology, but the correct and rapid diagnosis are essential to define strategies for the diseases management. Molecular techniques are able to amplify specific fragments from small amounts of genetic material and powerful tools widely used in various areas, including the phytopathological diagnosis. Several techniques have been studied and designed for the amplification of nucleic acids, including the LAMP (Loop-mediated isothermal amplification), which has high specificity, sensitivity and is fast. The aim of this study was to develop and optimize a specific molecular test for S. sclerotiorum by LAMP, as well as its validation to oilseed pare and soybean seeds samples. A set of six primers was designed and evaluated for S. sclerotiorum sensitivity and specificity detection. The composition of the LAMP reaction was enhanced for real-time (SS-qLAMP) and direct analysis (SS-cLAMP). The DNA from 57 isolates of S. sclerotiorum, DNA from several other plant pathogens and DNA from different cultures was tested. The DNA of all isolates of S. sclerotiorum were detected but no the other DNA samples. When testing the limit of detection of reactions, a single copy detections was suggested. By SS-qLAMP two curves were generated which can be used to estimate the amount of mycelium and DNA of S. sclerotiorum present in the samples analyzed. Bothe developed tests (SS-qLAMP and SS-cLAMP) can be applied to several purposes, such as detection of the pathogen in plant, spore traps, soil and seeds samples. Using seed samples with different contamination level, the test was optimized for canola and soybean seeds, SS-qLAMP(Canola) and SS-qLAMP(Soybean), respectively, detecting the presence of the pathogen in samples up to 0.13% and 0.03% naturally contaminated for canola and soybean, respectively, and was able to detect contamination in samples not contaminated according incubation-based methods. The time require for the test was 4h and 30 minutes and 2 hours and 50 minutes for canola and soybeans, respectively, with no needs of large space for samples incubation, specialized analysts and able to analyzed many samples simultaneously. The proposed method SS-qLAMP was well-validated according the ISTA (International Seed Testing Association) rules to oilseed-rape and soybean seed samples. x